TINJAUAN HUKUM PIDANA ISLAM TERHADAP PUTUSAN HAKIM DALAM TINDAK PIDANA PENYUAPAN YANG DILAKUKAN OLEH BADAN HUKUM (Studi Putusan Nomor 26/pid.sus-TPK/2019/PN Plg) - Adelia Fitriyani; Romli SA; Antoni Antoni (Universitas Islam Negeri Raden Fatah Palembang, 2021)
Research entitled Review of Islamic Criminal Law Against Judges Decisions in the Crime of Bribery Committed by Legal Entities (Decision Study No.26 / Pid.Sus-TPK / 2019 / PN Plg). The method used in this research is aapproach library research (library study). The type of data used is qualitative, as for the source of data taken in this study is the type of secondary data obtained from data that has been processed and obtained from library materials, according to the results of the study that according to the positive law on the review of judges' decisions in the crime of bribery carried out By a legal entity in case Number 26 / Pid.Sus-TPK / 2019 / PN Plg sentenced the defendant to imprisonment for 3 (three) years and a fine of Rp. 250,000,000.00 (Two Hundred Fifty Million Rupiah) provided that if the fine is not paid, it is replaced by imprisonment for 6 (six) months and the sanction against PT Indo Paser Beton is the blocking of all accounts in the name of the defendant, namely Robi Okta Fahlevi as the owner. company. Meanwhile, according to the Islamic Criminal Law Against Bribery Conducted by Legal Entities in case Number 26 / Pid-Sus-TPK / 2019 / PN Plg, namely the imposition of Ta'zir penalties whose type and size are the authority of judges and local authorities to determine them. Keywords: Crime, Bribery, Ta'zir